PEMBANGUNAN ZONA INTEGRITAS SEBAGAI UPAYA KEJAKSAAN TINGGI RIAU MEWUJUDKAN PREDIKAT WILAYAH BIROKRASI BERSIH DAN MELAYANI (WBBM) TAHUN 2024 - Oktaviani, Shinta Dwi; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Integrity zone development is an effort to realize bureaucratic reform aimed at creating a government institution that is clean, accountable, and service oriented. The Riau High Prosecutor's Office, as a law enforcement institution, actively participates in implementing integrity zones to achieve the Clean and Serving Bureaucracy Area (WBBM) title. This study aims to explore and explain the process of integrity zone development at the Riau High Prosecutor’s Office in 2024, the implementation of related policies and theories, as well as the challenges and developments encountered during its implementation. This research was conducted using a descriptive qualitative approach. Data collection techniques included interviews, documentation, and observation. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that the integrity zone development at the Riau High Prosecutor's Office is carried out through six areas of change: change management, organizational structuring, human resource management, strengthening accountability, strengthening supervision, and improving the quality of public services. This aligns with Dwiyanto’s theory of bureaucratic reform, which emphasizes the importance of transformation in organizational structure, improved human resource quality, simplification of procedures, enhanced supervision and accountability, and better public service delivery. The implementation of the integrity zone theory is carried out gradually, based on PERMEN PANRB Regulation No.90 of 2021. The Riau High Prosecutor's Office has also developed various innovations, including the use of information technology in public services, as part of its commitment to WBBM. However, several challenges remain, including the suboptimal score of the SAKIP, obstacles in simplifying service procedures, and the presence of internal behaviors that are inconsistent with the principles of integrity. Nevertheless, there have been significant positive changes in work culture and service systems, indicating that the integrity zone development process at the Riau High Prosecutor's Office is moving in a promising direction. Keywords: Integrity Zone, WBBM, Prosecutor’s Office, Bureaucratic Reform, Public Service